ANALISIS PENERAPAN PEMBIAYAAN SISTEM BAGI HASIL MUDHARABAH DAN MUSYARAKAH SERTA PERLAKUAN AKUNTANSINYA MENURUT PSAK 105 DAN 106 PADA LEMBAGA KEUANGAN SYARIAH (Studi Kasus pada Koperasi Murni Amanah Sejahtera Malang) - Fatima Tuzaroh; Afifudin Afifudin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis research was conducted to analyze the application of mudharabah and musyarakah profit sharing financing systems and its accounting treatment based on PSAK 105 and 106 on Islamic financial institutions in the Malang Amanah Sejahtera Cooperative. This study used a qualitative method. Based on the results of analysis used qualitative method show that Malang Amanah Sejahtera Cooperative was not fully implemented recognition, measurement, presentation and disclosure both PSAK 105 for Mudharabah Financing and PSAK 106 for Musyarakah Financing.Keywords: Mudharabah, Musyarakah, Mudharabah Accounting Treatment, and Musyarakah Accounting Treatment.